Lessons from Visualizing the Functions of the Building Enclosure - McGlohn, Emily M. (ARCC Conference Repository, 2014)
A study completed in 2012, by the author, surveyed designers and builders about their use and understanding of the air barrier system in residential construction. Results show that a larger percentage of builders than designers reported always performing blower door tests on their projects. The study also showed that a larger percentage of builders than designers believe that an air barrier system must be continuous to be effective. It is well known that an air barrier system must be continuous to be completely effective and it is hypothesized that more builders believe this because they have first hand, visual experience of air infiltration. Blower door tests depressurize a building to expose air leaks through theenclosure. If visualization of air infiltration has convinced more builders of the importance of the air barrier system, what other visual and experiential tests of the building enclosure could be devised for building professionals to reinforce the importance of other enclosure components? This paper explores possibilities for new experiential tests for a highly misunderstood layer of the enclosure,the vapor retarder. Reasons for its misunderstanding are numerous: placement is climate based, it issometimes only millimeters thick, it is made of many parts, information on the topic is often unreliable and itis generally a confusing topic. For these reasons, the vapor retarder is often misused within the enclosure creating potential problems for structural rot and mold within walls. Is there an onsite testing option for this layer that would provide the same visual feedback that the blower door test gives for the air barrier system? This paper seeks to identify possible methods to teach building professionals using hands on experience and visualization about the function of the vapor retarder.